Whose child is it anyway? Differential parental investments in education and children under kinship care in the Philippines - Joseph J. Capuno; Xylee Javier (University of the Philippines, School of Economics (UPSE), 2012)
While education is universally held to enhance a child human development, policies must still contend with parental biases. Here, we investigate if school attendance of young household members aged 6-12 years old varies with their kinship ties to the household heads in the Philippines. Applying probit regression techniques on a dataset culled from the five rounds of the Annual Poverty Indicators Survey, we find that the probability of attending school of the head's own child is about 2.9-percentage points greater that that other relatives in the same age group, controlling for income and other factors. However, there are no differences in the likelihood of school attendance between the head's own grandchildren and other relatives. Thus, policies should target children under kinship care since household heads are unlikely to treat them like their own, even if they can afford to send these children to school.
Keywords: 330; Kinder; Bildungschancen; Bildungsverhalten; Eltern; Philippinen